2015
DOI: 10.33736/jcest.147.2015
|View full text |Cite
|
Sign up to set email alerts
|

Improving the strength performance of high volume periwinkle shell ash blended cement concrete with sodium nitrate as accelerator

Abstract: The objective of this study is to examine the effect of accelerator (NaNO3) on the strength properties of High volume Periwinkle shell ash blended cement concrete. A mix ratio and water-binder ratio of 1:2:4 (cement: sand: gravel) and 0.60, respectively was used as the reference. The cement was then replaced with 30% Periwinkle Shell Ash (PSA) by weight of cement. Sodium nitrate in the dosages of 1, 2, and 3% by weight of cement was added to the blended mixture of cement and PSA. The strength properties invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…Moreover, 30% replacement of sharp sand by PSA was a satisfactory mixture ratio for lowcost/lightweight buildings as well as 6.8% costsavings [50,51]. The results also agreed with the research findings of several previous publications [34,40,47]. Moreover, the cost savings were low compared to an earlier finding that made savings of 14-17% using 35-42% PSA [36].…”
Section: Shell In Concretessupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, 30% replacement of sharp sand by PSA was a satisfactory mixture ratio for lowcost/lightweight buildings as well as 6.8% costsavings [50,51]. The results also agreed with the research findings of several previous publications [34,40,47]. Moreover, the cost savings were low compared to an earlier finding that made savings of 14-17% using 35-42% PSA [36].…”
Section: Shell In Concretessupporting
confidence: 87%
“…Although research findings confirmed that NaNO 3 can improve the compressive strength and splitting strength performances of concretes [47], nevertheless it was sufficient to be classified as a load-bearing concrete. Hence, advances in concrete developments to achieve pillar strength status and weight/load bearing status are required for the improvement of PSP and PSA blended concretes.…”
Section: Review Methodologymentioning
confidence: 86%
See 1 more Smart Citation
“…The increasing rate of production has consequentially led to increased generation of waste shells. Shells such as periwinkle have in the past years been used by locals for minor constructions in the Niger-Delta regions [42][43][44], while a majority is continuously accrued and abandoned in open lands, constituting in environmental pollution.…”
Section: Shellfish Production In Nigeriamentioning
confidence: 99%
“…Seashells are primarily composed of CaCO 3 [12]. As such, recycling has been widely studied as a source of CaCO 3 or as CaO [16][17][18][19][20][21]. Seashell wastes were used in 15th-century Latin America as a raw material for the manufacture of Tabby concrete [22].…”
mentioning
confidence: 99%